Remote Instrumentation for eScience and Related Aspects - Davoli, Franco; Lawenda, Marcin; Meyer, Norbert; Pugliese, Roberto; Węglarz, Jan; Zappatore, Sandro (Springer New York : Imprint: Springer, 2012)
Making scientific instruments a manageable resource over distributed computing infrastructures such as the grid has been a key focal point of e-science research in recent years. It is now known by the generic term 'remote instrumentation', and is the subject of this useful volume that covers a range of perspectives on the topic reflected by the contributions to the 2010 workshop on remote instrumentation held in Poznań, Poland. E-science itself is a complex set of disciplines requiring computationally intensive distributed operations, high-speed networking, and collaborative working tools. As such, it is most often (and correctly) associated with grid- and cloud-computing infrastructures and middleware. The contributions to this publication consider broader aspects of the theme of remote instrumentation applied to e-science, as well as exploring related technologies that enable the implementation of truly distributed and coordinated laboratories. Among the topics discussed are remote instrumentation and sensors' infrastructure, virtual laboratories and observatories, architectural middleware elements, advanced grid and cloud computing, virtual machines, and software platforms. As the potential fruits of distributed e-science enquiry expand, this book enables researchers in the sector to keep abreast of very latest developments.